Design and synthesis of some novel hydrazide, 1,2-dihydropyridine, chromene derivatives carrying biologically active sulfone moieties with potential anticancer activity - Bashandy, Mahmoud S; Al-Said, Mansour S.; Al-Qasoumi, Saleh I.; Ghorab, Mostafa M. (Arzneimittelforschung, 2011)
This paper describes the synthesis of some novel sulfones having biologically active hydrazides (4-9, 22, 23, 26 and 27), hydrazonoyl cyanide (24), 1,2-dihydro-pyridines (16-21), chromene (28) and benzochromene (29) moieties starting with 1-[4-(piperidin-1-ylsulfonyl)phenyl]-ethanone 1. The structures of the the newly synthesized compounds were confirmed by elemental analysis, IR, 1H NMR and 13C NMR. All the newly synthesized compounds were evaluated for their in vitro anticancer activity against breast cancer cell line (MCF7).
Keywords: Anticancer activity; Breast cancer cell line; Chromene derivatives; 1,2-Dihydropyridine; Hydrazide derivatives; Sulfone derivatives